The study of Yi minority language in Mengzi from the perspective of eco-linguistics - Yu, JianBin; Ng, Boon Sim; Mamat, Roslina (Richtmann Publishing, 2023)
The Yi language is a unique language spoken by the Yi minority in China. Despite Mengzi City having one of the largest Yi populations in Yunnan Province, there are very few studies about the Yi language from an ecolinguistics perspective in this region. The primary aim of this study is to investigate language competence, language use, and language attitudes among young people aged 14-28 from Mengzi. Fieldwork research was conducted to collect data, which involved administering a series of questionnaires, interviews, and observations with a group of 104 Yi teenagers. Research findings highlighted that the language ecology in the Mengzi region is changing, with the original mother tongue-dominant type gradually shifting toward a Chinese-dominant type. Although 58.6% of participants claimed fluency or semi-fluency in the Yi language, only 18.8% of them could read and write Yi characters. Due to its inferior status in modern society, the use of the Yi language was limited to family and religious domains. Furthermore, although participants showed a positive inclination toward the Yi language, they held a higher regard for the status and function of Chinese (Mandarin). In conclusion, external forces motivating young speakers to shift from their native language to Mandarin encompass social and economic advancement, as well as national language policies. The significance of the study lies in documenting Yi’s mother tongue and its role in raising awareness about the preservation of endangered languages in China.